The Merit System Development to Actualising Career Establishment of Civil Apparatus in East Java Province Government - Nidaul Hidayah; Nuri Herachwati (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This research determines the civil servant's career development after implementing the merit system in the East Java Provincial Government. This research took place at the East Java Province Regional Personnel Agency in Planning, Procurement, Data Processing, and ASN Information Systems. The descriptive qualitative approach was used in this study to determine professional personnel management with civil servant placement and government officials by applying performance competencies and track records as measurement instruments. However, the merit system has not been optimized by the Regional Government. If this system is fully implemented, local governments can obtain professional figures who have good performance. The practices that come off are the politicization of the State Civil Apparatus (ASN). The new regional leader usually exposes the staff along with their acquaintance or election success team. Everything is still related to returning the favor or revenge. So, it is necessary to apply a merit system in independent Local Government administration that is KKN-free. This research explored how the Merit System implementation in State Civil Apparatuses affects career growth and how the elements influencing Merit System application can increase transparency in ASN career development. The goal of this research is to create a professional environment within the regional government.